2019
DOI: 10.1001/jamadermatol.2018.4645
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Subsequent Primary Melanomas in Austria

Abstract: on risk factors of subsequent melanomas would be helpful to identify patients at risk after the diagnosis of their first melanomas. OBJECTIVE To determine risk factors of subsequent melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 43 publications
4
42
1
Order By: Relevance
“…Moreover, the authors noted that disentangling risk from use of sunbeds from that of the sun is difficult [anecdotal attribution of melanoma to sunbed use is often offset by excessive sunbathing, as exemplified by an Australian publicity campaign to regulate solaria (16)]. The importance of solar UV exposure and sunburn for melanoma development is reflected by the frequency of melanomas that occur after the diagnosis of a cutaneous melanoma, reported to range from 8.2% of previously diagnosed melanoma in European countries to 23% in countries with more intense ambient solar UV radiation (34)(35)(36)(37)(38)(39)(40)(41)(42). Earlier studies identified the number of sunburns as a good proxy of "at risk" sun exposure in relation to melanoma (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the authors noted that disentangling risk from use of sunbeds from that of the sun is difficult [anecdotal attribution of melanoma to sunbed use is often offset by excessive sunbathing, as exemplified by an Australian publicity campaign to regulate solaria (16)]. The importance of solar UV exposure and sunburn for melanoma development is reflected by the frequency of melanomas that occur after the diagnosis of a cutaneous melanoma, reported to range from 8.2% of previously diagnosed melanoma in European countries to 23% in countries with more intense ambient solar UV radiation (34)(35)(36)(37)(38)(39)(40)(41)(42). Earlier studies identified the number of sunburns as a good proxy of "at risk" sun exposure in relation to melanoma (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…Suppa and Gandini mentioned the study, but the main findings were not adequately presented (1). In that study, solarium use was not associated with an increased but rather a reduced risk for developing melanoma (OR=0.71; 95% confidence interval=0.51-0.99; p=0.04) (34). Those findings indicate that solarium use may even have a protective effect.…”
Section: Inconsistent Findings Observed By Different Persons Differenmentioning
confidence: 86%
See 1 more Smart Citation
“…Family history comprises approximately 5-15% of melanoma cases; however, this does not imply that a single genetic mutation is being transmitted [4]; shared sun exposure and other risk factors are more plausible causes of melanoma among families with susceptible skin types [3]. Patients diagnosed with a single primary melanoma are at an increased risk of developing subsequent primary melanomas, which most likely occur within two years after the first diagnosis [5]. In fact, this has been demonstrated for 70% of melanoma patients who developed a second primary melanoma, showing the importance of close skin surveillance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Non-melanoma skin cancer, other cancer types, gender, race, a higher number of nevi (especially dysplastic nevi), actinic skin damage, and family history of melanoma are all risk factors for hereditary melanoma [5,7]. Furthermore, hereditary melanoma has been associated with germline mutations in high-risk melanoma susceptibility genes (CDKN2A, CDK4, TERT, POT1) [8][9][10][11][12][13], polymorphisms in intermediate-risk melanoma susceptibility genes (BAP1, ACD, TERF2IP, MC1R and MITF) [14][15][16], and germline missense substitutions in MITF [17].…”
Section: Introductionmentioning
confidence: 99%